섬유소재 녹화시스템 적용에 따른 노후건축물 에너지 저감효과 분석 -열관류율 모니터링 분석을 중심으로 - 김태한; 이소담; 박정현; Kim, Tae-Han; Lee, So-Dam; Park, Jeong-Hyeon (KIEAE Journal, 17(6), 2017)
Purpose : Recently, community-led "city regeneration new deal projects" have been newly initiated, which avoid large-scale demolition while setting up small-scale, resident-oriented facilities needed for daily life. Method : This project is usually applied to obsolete buildings where living environment is poor and thus often needs to increase the insulation performance of building exterior coverings to reduce cooling and heating burden as well as generate environment improvement effects to residents who may be classified as an energy poverty segment. Given this, the application of afforestation system to buildings may be regarded as an alternative that meet these requirements, and objective performance check through long-term monitoring is necessary for extensive utilization. Through one-year, long-term monitoring of replicated obsolete buildings that have poor insulation performance, this study analyzed heat transmission coefficient improvement effect and daily average power consumption reduction effect expected when the afforestation system is applied. Result : By applying the afforestation system, heat transmission coefficient has improved by $0.10W/m^2$ on average. As for seasonal reduction efficiency, it improved 411~1,067kWh in summer at 22.6~33.1% reduction rate, which was higher than in winter.